2018
DOI: 10.1101/267682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tripsacum de novotranscriptome assemblies reveal parallel gene evolution with maize after ancient polyploidy

Abstract: Core Ideas Maize genes with protein evidence have higher expression and GC content Tripsacum homologs of maize genes exhibit the same trends as in maize Maize proteome genes have more highly correlated gene expression with Tripsacum Expression dominance for homeologs occurs similarly between maize and Tripsacum homologs A similar set of genes may be decaying into pseudogenes in maize and Tripsacum Plant genomes reduce in size following a whole‐genome duplication event, and one gene in a duplicate gene pair c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…A total of 1259 high quality consensus sequences from T. dactyloides failed to map to maize reference genome, which was generated from the maize inbred B73. This number is roughly consistent with another report of 1737 T. dactyloides transcripts that lack orthologs in the maize genome (Gault et al ., ). Sequences that lacked apparent homologs in the maize reference genome were aligned to NCBI's RefSeq plant database.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…A total of 1259 high quality consensus sequences from T. dactyloides failed to map to maize reference genome, which was generated from the maize inbred B73. This number is roughly consistent with another report of 1737 T. dactyloides transcripts that lack orthologs in the maize genome (Gault et al ., ). Sequences that lacked apparent homologs in the maize reference genome were aligned to NCBI's RefSeq plant database.…”
Section: Resultsmentioning
confidence: 97%
“…While widely grown in temperate regions over the summer, maize remains sensitive to cold. Maize varieties with the ability to be planted significantly earlier, or in the extreme case to overwinter, have the potential to intercept a greater proportion of total annual solar radiation increasing maximum potential yields (Dohleman and Long, ; Gault et al ., ). It must be acknowledged that there are many other differences in niches, environments, and selective pressures experienced by T. dactyloides and the environments and selective pressures experienced by maize and its wild progenitors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Whole genome duplication can generate the raw materials for the maintenance of genetic diversity (Wendel, 2000; Adams and Wendel, 2005). Gault et al (2018) demonstrated that similar sets of duplicated genes were preserved in two related genera, Zea and Tripsacum , millions of years after a shared paleopolyploidization event. This conserved pattern in purifying selection suggests that, at least for some genes, there is a clear advantage to maintaining two copies.…”
Section: Introductionmentioning
confidence: 99%